2004
DOI: 10.1007/s11095-004-7668-4
|View full text |Cite
|
Sign up to set email alerts
|

The Rate of Drug Particle Detachment from Carrier Crystals in an Air Classifier-Based Inhaler

Abstract: Drug detachment from carrier approaches first-order reaction within the first half-second of inhalation. But at longer circulation times in the classifier, the ratio of removal to adhesive forces decreases dramatically. To increase the detached fraction of drug during inhalation at a constant flow rate, a short residence time for the powder in the de-agglomerator between 0.5 and 2 s is desired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 34 publications
1
29
0
Order By: Relevance
“…There have been several reports on the relationship between peak inspiratory flow rate and drug deposited by various systems, 3,4) with a Diskhaler shown to deliver approximately 12% of the initial dose. 11,12) The present results support and confirm those previous studies, as the estimated amount of drug deposited in stage 2 was 10.1 mg at a flow rate of 60 l/min, adequate for obtaining a good effect from a Diskhaler and similar to the 12% reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been several reports on the relationship between peak inspiratory flow rate and drug deposited by various systems, 3,4) with a Diskhaler shown to deliver approximately 12% of the initial dose. 11,12) The present results support and confirm those previous studies, as the estimated amount of drug deposited in stage 2 was 10.1 mg at a flow rate of 60 l/min, adequate for obtaining a good effect from a Diskhaler and similar to the 12% reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…The curves generated from the estimated values were well matched to the values obtained in the experiment. (3) The doses deposited in stage 2 were estimated to be 2.9 mg at a flow rate of 20 l/min, 6.6 mg at 30 l/min, 8.4 mg at 40 l/min, 10.1 mg at 60 l/min, and 11.3 mg at 90 l/min.…”
Section: Analysis Of Relationship Between Amount Of Drug Released Fromentioning
confidence: 99%
See 1 more Smart Citation
“…1). (1) Next, the relationship between the amount of drug released from the device and amount deposited in stage 2 was analyzed. The amount of drug deposited in stage 2 was calculated from the peak inspiratory flow rate, by integration of Eq.…”
Section: Relationship Between Amount Of Drug Released From Fp-dh and mentioning
confidence: 99%
“…Further, it has been proposed that the inspiratory ability of the patient has an influence on the amount remaining in the device. 1,2) Since dosing performance of an FP-DH is likely dependent on patient inspiration capability, the method of inhalation is important clinically for delivery of the proper dosage. In our previous study, patients found some amounts of drugs remaining in the device after a single inhalation with an FP-DH, while those remaining after a second inhalation were decreased by tapping the device after the first inhalation.…”
mentioning
confidence: 99%